2021
DOI: 10.3390/math9192401
|View full text |Cite
|
Sign up to set email alerts
|

Blood Clotting Decreases Pulmonary Circulation during the Coronavirus Disease

Abstract: Spontaneous blood clotting in pulmonary circulation caused by thrombo-inflammation is one of the main mortality causes during the COVID-19 disease. Blood clotting leads to reduced pulmonary circulation and blood oxygenation. Lung inflammation can be evaluated with noninvasive diagnostic techniques. However, the correlation of the severity of the inflammation with the pulmonary blood flow has not been established. To address this question, in this work, we develop a multiscale model taking into account the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The model has shown that the lack of antithrombin and the excess of fibrinogen significantly influence the risk of thrombosis. In a previous study, we used a multiscale model to quantify the effect of vessel obstruction on blood circulation as a result of lung inflammation in COVID-19 [26]. We showed that an obstruction level of 5% leads to a decrease in blood flux by 12%.…”
Section: Introductionmentioning
confidence: 96%
“…The model has shown that the lack of antithrombin and the excess of fibrinogen significantly influence the risk of thrombosis. In a previous study, we used a multiscale model to quantify the effect of vessel obstruction on blood circulation as a result of lung inflammation in COVID-19 [26]. We showed that an obstruction level of 5% leads to a decrease in blood flux by 12%.…”
Section: Introductionmentioning
confidence: 96%